2007
DOI: 10.1002/adfm.200600484
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Ground‐State Charge‐Transfer Complex in Polyfluorene//[6,6]‐Phenyl‐C61 Butyric Acid Methyl Ester (PCBM) Blend Films and Its Role in the Function of Polymer/PCBM Solar Cells

Abstract: Evidence is presented for the formation of a weak ground‐state charge‐transfer complex in the blend films of poly[9,9‐dioctylfluorene‐co‐N‐(4‐methoxyphenyl)diphenylamine] polymer (TFMO) and [6,6]‐phenyl‐C61 butyric acid methyl ester (PCBM), using photothermal deflection spectroscopy (PDS) and photoluminescence (PL) spectroscopy. Comparison of this polymer blend with other polyfluorene polymer/PCBM blends shows that the appearance of this ground‐state charge‐transfer complex is correlated to the ionization pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
261
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(278 citation statements)
references
References 29 publications
15
261
0
2
Order By: Relevance
“…Previous studies of PPV and polyfluorene-based donor/acceptor blends 29,35,36,86,87 have reported significant red-shifted exciplex-like emission and CT absorption, suggesting that the BRP states observed in these systems are radiatively coupled to the ground state. A sub-band gap absorption has also been reported for P3HT/PCBM blend films by Fourier-transform photocurrent spectroscopy.…”
Section: -----<<< Scheme 1 >>>-----mentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies of PPV and polyfluorene-based donor/acceptor blends 29,35,36,86,87 have reported significant red-shifted exciplex-like emission and CT absorption, suggesting that the BRP states observed in these systems are radiatively coupled to the ground state. A sub-band gap absorption has also been reported for P3HT/PCBM blend films by Fourier-transform photocurrent spectroscopy.…”
Section: -----<<< Scheme 1 >>>-----mentioning
confidence: 92%
“…Similar observations have been made for polyfluorene-based polymer/polymer blend films 35 and for polyfluorene/fullerene blends. 36 In particular, in a study employing three different PPV-based polymers, an inverse correlation was observed between this exciplex-like emission strength and PV device performance. 32 However, a clear understanding of the parameters determining the efficiency of charge dissociation versus geminate recombination in organic blend films is yet to be established.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, the existence of an intermediate charge transfer (CT) state between the exciton and the free charges in some blend systems based on polyfluorene has been reported. [62][63][64] Understanding the nature of such an intermediate state and its dependence on blend composition is important in understanding the effect of microstructure on charge generation. As an example, Veldman et al confirmed the existence of a charge transfer (CT) state in the blend of a fluorene copolymer (PF10TBT) ''poly[2,7-(9,9-dialkylfluorene)-alt-5,5-(4 0 ,7 0 -di-2-thienyl-2 0 ,1 0 ,3 0 -benzothiadiazole)] with PCBM.…”
Section: Blend Compositionmentioning
confidence: 99%
“…By comparing PDS signal of the polymer:fullerene blend with those of the individual components, weak absorption from the CT state was observed (Figure 2a), indicating interaction between polymer and fullerene in the ground state. [35][36][37] In addition to PDS, we can also detect the CT state absorption by measuring the external quantum efficiency (EQE) of the solar cell in the CT state absorption regime, where neither polymer nor fullerene absorbs. The EQE in the CT state absorption regime results from the photocurrent generated by absorption of the CT state.…”
Section: Absorptionmentioning
confidence: 99%